Studying the Effect of Placenta and Neurotissue on Membrane Metabolic Function of Rat’s Liver Mitochondria and Microsomes in vitro - Strona, V. I.; Yurchenko, T. N.; Ryazantsev, V. V.; Shepitko, V. I.; Prokopyuk, O. S.; Gordienko, A. I. (Problems of Cryobiology and Cryomedicine, 2002)
In the models of enzymic ascorbate-dependent lipid peroxidation (LPO) of microsomes and using the estimation of metabolic state of rat’s liver mitochondriaa in vitro the authors have studied antioxidative properties of placenta and neurotissue preparations. Existing cryotechnology of obtaining and storage of biopreparations based on placenta and nerve tisue provides a high content of.